2020
DOI: 10.1542/peds.2019-3870
|View full text |Cite
|
Sign up to set email alerts
|

Severe Maternal Morbidity and Infant Mortality in Canada

Abstract: BACKGROUND: Severe maternal morbidity (SMM) comprises an array of conditions and procedures denoting an acutely life-threatening pregnancy-related condition. SMM may further compromise fetal well-being. Empirical data are lacking about the relation between SMM and infant mortality.METHODS: This population-based cohort study included 1 892 857 singleton births between 2002 and 2017 in Ontario, Canada, within a universal health care system. The exposure was SMM as an overall construct arising from 23 weeks' gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…To assess the validity and comparability of state-level SMM rates, we examined state-level associations between SMM and other perinatal indicators that may contribute to (eg, prepregnancy hypertension, diabetes, and obesity and low-risk cesarean delivery), coincide with (eg, preterm birth), or result from (eg, maternal and infant mortality) SMM. 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…To assess the validity and comparability of state-level SMM rates, we examined state-level associations between SMM and other perinatal indicators that may contribute to (eg, prepregnancy hypertension, diabetes, and obesity and low-risk cesarean delivery), coincide with (eg, preterm birth), or result from (eg, maternal and infant mortality) SMM. 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies also demonstrated that high-risk pregnancy had an ambiguous association with perinatal mortality [ 12 , 14 ]. Even in well developed countries, severe maternal morbidities conferred increased risks of infant mortality [RR 2.93 (2.51, 3.41)] [ 37 ]. In-depth analyses are needed to explore the severity of maternal morbidities in relation to infant outcome in resource-limited, evolving regions and countries.…”
Section: Discussionmentioning
confidence: 99%
“…This study builds upon the sparse existing evidence that SMM is associated with infant health. One previous study of this relationship found associations between SMM and infant mortality and sepsis ( 4 ). This study used the standard CDC definition of SMM, which includes maternal readmissions up to 42 days after delivery, while our study restricted SMM to those cases identified during the delivery hospitalization in order to focus on infant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are currently little data on the effects of SMM on infant outcomes. Our literature search only identified one prior study that directly examined the association between SMM and infant health ( 4 ). The researchers used all births in Ontario from 2002 to 2017 and found that CDC-defined SMM was associated increased infant mortality and sepsis.…”
Section: Introductionmentioning
confidence: 99%